Unravelling the stomach contents of fish and crab species from Cananéia, São Paulo: Are they eating plastic? - Gonçalves, Geslaine Rafaela Lemos [UNESP]; Sousa, Aline Nonato [UNESP]; Wolf, Milena Regina [UNESP]; Soares, Isabel Matos [UNESP]; Castilho, Antonio Leão [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Plastic pollution represents a threat to marine ecosystems and has therefore been gaining space in the realm of pub-lic interest. In this study, we investigated the ingestion of food and non-food items (i.e., plastic particles) by fish and crabs. These animals are commonly collected by trawling with a double-ring net along the coast of Cananéia, state of São Paulo, Brazil; some of them are consumed as food by the local population. Fish and crab stomachs were removed and dissected, and their contents were examined under a stereoscopic microscope with an image-capturing system. The presence or absence of plastic was also registered. We examined 139 specimens of 16 fish species and 143 specimens of four crab species. The most frequent food items found in fish were unidentified food, followed by crustaceans, molluscs, polychaetes, and other fish; in crabs, the items were unidentified food, followed by crustaceans, molluscs and fish. Plastic particles were found in all fish species, representing 47.5% of the individuals analysed. In crabs, the incidence of plastic was lower, occurring in only two species (5% in Callinectes danae and 3% in C. ornatus). Only four fish species analysed had previous records of plastic ingestion in the scientific literature. The high incidence of microplastics in our study is worrying because they negatively affect the animals’ lives and can be transferred through the tropic web to top predators, including humans, through the ingestion of contaminated animals.
Keywords: Anthropogenic influence; Commercial fish; Human exposure; Plastic fibres